2004
DOI: 10.1111/j.1467-8624.2004.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Cocaine Exposure: A Comparison of 2‐Year‐Old Children in Parental and Nonparental Care

Abstract: Effects of prenatal cocaine exposure and parental versus nonparental care on outcome at 2 years of age were examined. The sample included 83 cocaine-exposed and 63 nonexposed children and their caregivers; 49 and 34 of the cocaine-exposed children experienced parental and nonparental care, respectively. Prenatal drug exposure was not related directly to children's outcome at 2 years of age. However, compared with cocaine-exposed children in parental care, those in nonparental care experienced a more optimal en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 58 publications
6
60
0
Order By: Relevance
“…Most investigators have also not found detrimental effects of PCE on infant motor development, as measured by the Psychomotor Development Index (PDI) of the BSID or by the Peabody Developmental Motor Scales [2][3][4]12,13,21,34,36,41,43,[58][59][60]65,83]. By contrast, Singer et al [82] found that PCE was associated with lower PDI scores at about 17 months.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Most investigators have also not found detrimental effects of PCE on infant motor development, as measured by the Psychomotor Development Index (PDI) of the BSID or by the Peabody Developmental Motor Scales [2][3][4]12,13,21,34,36,41,43,[58][59][60]65,83]. By contrast, Singer et al [82] found that PCE was associated with lower PDI scores at about 17 months.…”
Section: Introductionmentioning
confidence: 98%
“…There have been consistent reports of no detrimental effects of PCE on global cognitive development during infancy, as measured by the Mental Development Index (MDI) of the Bayley Scales of Infant Development (BSID [9] and BSID-II [10]) [4,12,13,20,21,32,36,41,43,48,[58][59][60]65]. Only a few studies have reported detrimental effects on MDI scores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No such differences were found. Because of the possibility that there might be group differences in outcome measures between exposed infants in foster care and exposed infants still in the custody of their biological mother (e.g., Brown et al, 2004), we conducted analyses to see if there were differences in HR or RSA for infants whose primary caregiver was the biological mother (n = 143) as compared to infants who were in the care of someone other than the biological mother (n = 11). There were no group differences for HR or RSA measures.…”
Section: Group and Gender Differences For Rsa And Hrmentioning
confidence: 99%
“…2 In contrast, others have found associations between PDE and behavior problems, 1,5 symptoms of oppositional defiant disorder and ADHD, 6 aggression, 7 task persistence and attention problems, 8,9 and language performance. 10 The inconsistent findings may be partially attributed to methodological inconsistencies and to failure to control for confounders, ranging from prenatal tobacco and alcohol exposure, [11][12][13][14] to parental and family variables, such as mental health, education, intelligence, and income. To ensure that variables contributing to children's functioning were identified and controlled, this investigation was guided by developmentalecological theory, 15 utilizing a bidirectional model whereby children are influenced by their proximal environment, including their family, peers, and schools, and in turn, impact their proximal environment through their behavior.…”
mentioning
confidence: 99%